2017
DOI: 10.1007/s10886-017-0860-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Host-Derived Volatiles for Trapping Culicoides Biting Midges (Diptera: Ceratopogonidae)

Abstract: Culicoides biting midges (Diptera: Ceratopognidae) cause pain and distress through blood feeding, and transmit viruses that threaten both animal and human health worldwide. There are few effective tools for monitoring and control of biting midges, with semiochemical-based strategies offering the advantage of targeting host-seeking populations. In previous studies, we identified the host preference of multiple Culicoides species, including Culicoides impunctatus, as well as cattle-derived compounds that modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…Traps were placed in middle of the field, and each trap was located 60 m from any other trap, so that the individual treatments were 60 m apart. To avoid cross-contamination, only one compound was tested at each sub-site at any time, and each compound was tested at only one sub-site ( Isberg et al, 2017 ). Each trap was set to operate from 1 h before sunset until 1 h after sunset.…”
Section: Methodsmentioning
confidence: 99%
“…Traps were placed in middle of the field, and each trap was located 60 m from any other trap, so that the individual treatments were 60 m apart. To avoid cross-contamination, only one compound was tested at each sub-site at any time, and each compound was tested at only one sub-site ( Isberg et al, 2017 ). Each trap was set to operate from 1 h before sunset until 1 h after sunset.…”
Section: Methodsmentioning
confidence: 99%
“…Surveillance has steadily been conducted in several countries to investigate the distribution of Culicoides that is a vector of arboviruses, and to test against target viruses for predicting the outbreak [ 2 , 22 , 23 ]. As these investigations have been carried out for a long time, haematophagous vector collection methods have been developed on a variety of occasions, such as collection means using UV light with a wide range of wavelengths [ 24 ], and traps in which carbon dioxide (CO 2 ) is released at diverse concentrations to attract Culicoides [ 25 ]. They showed that the standard CDC UV light trap collected the Culicoides significantly more than the normal LED trap, and CO 2 trap releasing decanal or phenol collected highly compared to trap with CO 2 alone.…”
Section: Discussionmentioning
confidence: 99%
“…These results will be a useful source to collect Culicoides more effectively. In addition, new species of Culicoides as a vector of arboviruses are continuously being discovered [ 25 27 ]. In Korea, new Culicoides species were discovered in 2013 [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The release rate of 500 ml/min used is similar to that applied previously to trap biting midges (Cilek and Kline 2002, Mands et al 2004, Harrup et al 2012). The third baiting system tested was the Model 1012‐CO 2 with CO 2 release supplemented with 100 μl 1‐octen‐3‐ol (racemic mixture, 98 % pure, Sigma‐Aldrich Chemie GmbH, Steinheim, Germany), released through holes (16 mm Ø) drilled in the lids of three polyethylene vials (Kartell, Noviglio, Italy; H: 32.9 mm, Ø: 22.8 mm (Isberg et al 2017)). This resulted in a release rate of 6 mg/h, similar to that used in previous studies (Ritchie et al 1994, Mands et al 2004).…”
Section: Methodsmentioning
confidence: 99%
“…This resulted in a release rate of 6 mg/h, similar to that used in previous studies (Ritchie et al 1994, Mands et al 2004). The release system was developed in a preliminary study in which vials were weighed at 6 h intervals during continuous outdoor exposure to temperatures equivalent to field‐trapping conditions (Isberg et al 2017). Vials were attached to the trap using a metal wire at a point adjacent to the tube releasing the CO 2 and were replaced every 24 h. The fourth trap type used (Blacklight (UV) Model 1212.…”
Section: Methodsmentioning
confidence: 99%